2018
DOI: 10.1111/vsu.12936
|View full text |Cite
|
Sign up to set email alerts
|

Conservative versus surgical treatment of 21 sports horses with osseous trauma in the proximal phalangeal sagittal groove diagnosed by low‐field MRI

Abstract: The prognosis for return to athletic functions in horses with osseous trauma within the proximal aspect of the PP is guarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…This is in agreement with the recent literature in the human field [3]. Others have proposed to use ‘high fluid signal’ to describe the feature associated with replacement of fat by water [8]. In the present study the term BMO-‘type’ (BMO-t) is chosen in reference to a study of Thoroughbred fetlock using standing magnetic resonance imaging (sMRI) by Powell [12].…”
supporting
confidence: 74%
See 2 more Smart Citations
“…This is in agreement with the recent literature in the human field [3]. Others have proposed to use ‘high fluid signal’ to describe the feature associated with replacement of fat by water [8]. In the present study the term BMO-‘type’ (BMO-t) is chosen in reference to a study of Thoroughbred fetlock using standing magnetic resonance imaging (sMRI) by Powell [12].…”
supporting
confidence: 74%
“…It is expected that placement of screw may enhance healing through compression along the damaged bone, and minimize the risk of further microcrack propagation. Recently, Lipreri et al reported that there were no statistically significant differences between the conservative and surgical treatment groups by comparing the outcome of 21 sports horses diagnosed as having osseous trauma within the proximal aspect of P1 [8]. In the current study, majority of the horses returned to racing without surgery.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…A significant change in mineral density is required to detect OCLL in the femoral condyles (Bonilla et al ). However, undetected OCLLs may have a significant impact on treatment and prognosis (Bonilla et al ; Gold et al ; Lipreri et al ). In general, bone pathology was less frequently observed as compared to soft‐tissue pathology which may be related to advanced age of patients and chronicity of the lameness.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective study by Giulia Lipreri and colleagues in the UK compared outcomes following conservative vs. surgical management of sports horses with subchondral bone trauma of the proximal aspect of the proximal phalanx (PP) diagnosed by low‐field magnetic resonance imaging (MRI) .…”
Section: Subchondral Bone Traumamentioning
confidence: 99%